Deiksis dalam Novel London Love Story Karya Tisa Ts - Maulidiyah, Hikmatul; Haerussaleh, Haerussaleh; Huda, Nuril (GERAM, 2024)
The aim of this study is to analyze the three deixis in the novel London Love Story by Tisa Ts. The three deixis include person deixis, time deixis and place deixis. This study applies a qualitative descriptive methodology. The information contained in this study contains words and utterances that contain deixis available in the novel London Love Story by Tisa Ts. The technique applied in this study to combine data is documentation, this method is a method of collecting information by examining written, verbal and image documents. Based on the data analyzed, the type of persona deixis is the most common type of deixis. Future studies could benefit from this study. Furthermore, it can be useful for readers to know persona deixis, time deixis and place deixis in the novel London Love Story by Tisa Ts.